Determination Analysis Of Village Owned Enterprise Sustainability - Fathima, Salsa Hanifatul; Susanto, Barkah; Yuliani, Nur Laila; Darmadi, Ravindra Ardiana; Utami, Pranita Siska (Accounting and Finance Studies, 2025)
Research Aims: The purpose of this study is to analyze the effect of improving work quality, increasing income and budget efficiency on the sustainability of Village Owned Enterprise businesses in Borobudur District. The problems that occurred in Village Owned Enterprise which experienced a decline in performance in Borobudur for several years after COVID-19, especially in 2022 and 2023. The decline was due to three main factors, namely the lack of increased expertise, income, and budget management. Design/methodology/approach: The method used in this study is quantitative research using primary data obtained through the distribution of questionnaires to Village Owned Enterprise managers in Borobudur District. The technique is used in collecting samples using the purposive sampling method. The analysis methods used include Validity Test, Reliability, Determination Coefficient, and multiple linear regression with F Test and t Test. Research Findings: The results of this study indicate that improving work quality has a positive effect on business continuity, as well as other variables, increasing income and budget efficiency also have a positive effect on the sustainability of Village Owned Enterprise. Theoretical Contribution/Originality: The contribution of this research is expected to provide input and become a reference for Village Owned Enterprise and the local government and it is hoped that it can be generalized in identifying key factors that influence business sustainability. The limitations of this study are that the data needed for the study are difficult to obtain due to the limited human resources of Village Owned Enterprise, because several Village Owned Enterprise have merged into one with Balkondes.